The impact of climate-adaptive city construction pilot policies on corporate ESG performance - Cao, Chen; Zhang, Xintong; Yu, Guilan (Frontiers in Public Health, 2025)
IntroductionIn the context of climate-adaptive urban construction policies, understanding their impact on corporate sustainability practices is of critical importance. This study investigates how such policies influence corporate Environmental, Social, and Governance (ESG) performance.MethodsA multi-period difference-in-differences (DID) approach combined with text mining techniques was employed to evaluate the effects of climate-resilient city construction policies on corporate ESG performance. To ensure robustness, additional analyses were conducted using Propensity Score Matching-Difference-in-Differences (PSM-DID), instrumental variable methods, and various robustness checks.ResultsThe findings demonstrate that climate-resilient city construction policies significantly improve corporate ESG scores, thereby promoting sustainable development practices within companies. Mechanism analysis further reveals that managerial environmental awareness serves as a critical mediating factor, suggesting that the policies indirectly enhance ESG performance by increasing managers’ focus on environmental issues.DiscussionThis study provides empirical evidence that climate-adaptive urban construction policies contribute to improved corporate ESG outcomes. The results offer valuable insights for policymakers and practitioners, serving as a reference for the implementation of climate-resilient policies and for future theoretical and applied research on ESG performance.